Mary, the Type of the Church in the Johannine Writings: A Biblico — Theological Analysis - Nereparampil, Lucius (Journal of Dharma, 1996)
Mary Panthapallil, S.H., Mary, the Type of the I Church in the Johannine Writings : A Biblico — Theological Analysis. Kottayam: Oriental Institute of Religious Studies India Publications, 1996, pp. 274.